Detection of the Omicron BA.2.75 subvariant in Japan - Hirotsu, Yosuke; Omata, Masao (The Journal of infection, 2023)
•New emergent Omicron BA.2.75 subvariant was detected in Japan.•Familial transmission occurred and family members had no history of overseas travel.•Phylogenetic analysis likely showed the community-acquired infection of BA.2.75.